Nelson W. Aldrich papers - Aldrich, Nelson W. (Nelson Wilmarth), 1841-1915.; Aldrich, Abby Pearce Chapman, 1845-1917.
Correspondence, journal (1906) relating to the Hepburn bill, appointment books (1906-1909), drafts of speeches with related notes and memoranda, personal bank accounts, bills, receipts, and other financial papers, tariff schedules (1880-1894), documents, reports, bills, scrapbooks, clippings, pamphlets and other printed material chiefly relating to Aldrich's career as U.S. representative and senator from Rhode Island. Includes diaries (1904 and 1912) kept by Aldrich's wife, Abby Pearce Chapman Aldrich; biographical material concerning the Aldrich (Aldridge) family dating from 1762; and a group of biographer's papers (1924-1930) containing correspondence and notes of Jeannette Paddock Nichols and Nathaniel W. Stephenson. Correspondents include Henry B. Anthony, Johnson Newlon Camden, Henry White Cannon, Jonathan Chace, Charles F. Choate, Winthrop Murray Crane, Eugene Hale, Henry Cabot Lodge, William Thomas Nicholson, John D. Rockefeller, Theodore Roosevelt, William H. Taft, and William Whitman.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. representative and senator from Rhode Island, financier, and philanthropist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index to Series 1: Diaries and Notebooks, 1863-1927; and Series 2: General Correspondence, 1777-1915, available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthony, Henry B. -- 1815-1884 -- Correspondence; Camden, Johnson Newlon, -- 1828-1908 -- Correspondence; Cannon, Henry White, -- 1850-1934 -- Correspondence; Chace, Jonathan, -- 1829-1917 -- Correspondence; Choate, Charles F. -- 1828-1911.; Crane, Winthrop Murray, -- 1853-1920 -- Correspondence; Hale, Eugene, -- 1836-1918 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Nichols, Jeannette Paddock, -- 1890- -- Correspondence; Nicholson, William Thomas, -- 1834-1893 -- Correspondence; Rockefeller, John D., -- Jr. -- 1874-1960.; Roosevelt, Theodore, -- 1858-1919.; Stephenson, Nathaniel W. -- 1867-1935 -- Correspondence; Taft, William H. -- 1857-1930.; Whitman, William, -- 1842-1928 -- Correspondence; Aldridge family; Tariff -- United States; Rhode Island -- Politics and government -- 1865-1950.; Hepburn Act, 1906.; Financiers; Philanthropists; Representatives, U.S. Congress -- Rhode Island; Senators, U.S. Congress -- Rhode Island